Accuracy in Self-Reported Health Insurance Coverage among Medicaid Enrollees - Kathleen Thiede Call; Gestur Davidson; Michael Davern; E. Richard Brown; Jennifer Kincheloe; Justine G. Nelson (SAGE Publishing, 2008)
The largest portion of the Medicaid undercount is caused by survey reporting error-that is, Medicaid recipients misreport their enrollment in health insurance coverage surveys. In this study, we sampled known Medicaid enrollees to learn how they respond to health insurance questions and to document correlates of accurate and inaccurate reports. We found that Medicaid enrollees are fairly accurate reporters of insurance status and type of coverage, but some do report being uninsured. Multivariate analyses point to the prominent role of program-related factors in the accuracy of reports. Our findings suggest that the Medicaid undercount should not undermine confidence in survey-based estimates of uninsurance.